Social determinants of a Quilombola Community and its interface with Health Promotion - Michelle Kuntz Durand; Ivonete Teresinha Schülter Buss Heideman
ABSTRACT Objective: Understanding the relationship of social determinants in the Health Promotion of quilombola women. Method: This was a participatory study developed through the Research Itinerary of Paulo Freire, which comprises three stages: thematic investigation, codification and decoding, and critical unveiling. These stages were developed in Culture Circles from April to June 2016. Twenty themes were investigated, coded and decoded into eight themes, revealing the theme of women and their relationship with the Social Determinants. Results: Ten women from a quilombola community in Santa Catarina participated. The Health Promotion of this population and its interface with Social Determinants were understood. Health, religiosity, racial issues, social and community networks emerged as potentializing community empowerment and solidification. Conclusion: An accentuated correlation of racial issues and fragility combined with health care, education and information, and above all the distancing of vulnerable communities from comprehensive and equitable health was observed, highlighting the imminent need to strengthen Health Promotion strategies.